On the way to the Christian-Jewish dialogue (based on the materials published in “Kyiv Theological Academy Studies” journal (1860–1917)) - Vadym Menzhulin (Наукові записки НаУКМА: Філософія та релігієзнавство, 2018)
“Beilis affair” (1911–1913) is one of the most resonate events in Kyiv of the early 20 th century. It was a subject of a huge number of investigations. However, a special analysis of the role that the members of Kyiv Theological Academy community played in this affair has not been made yet. Facts and data available require further reflections and deeper interpretations. For this, both a time span and a thematic content should be expanded. Thus, the author tries to reveal the specifics of the discourse wherein the members of the community were predisposed to interpret both “Beilis affair” and “Jewish question” as a whole. The materials published in “Kyiv Theological Academy Studies” journal throughout all years of its existence in pre-revolutionary Russia (1860–1917) constitute the main source of information. In the study, the author tries to widen another researcher’s idea that “Beilis affair” became a unique case of the dialogue between Christians and Jews. The article shows that the foundations for this dialogue had been created in the previous years by many Kyiv Theological Academy community members, such as Andrii Khoinatskyi, Fedir Ornatskyi, Vasyl Pevnytskyi, Afanasii Bulhakov, Dmytro Bohdashevskyi, Olexandr Voronov, Mykola Stelletskyi, Viktor Ivanytskyi, Hryhorii Malevanskyi, Akym Olesnytskyi, and others. This experience as well as perfect knowledge of the European and world context, which the members of Kyiv Theological Academy intellectual community such as Olexandr Hlaholiev and Pavlo Tykhomyrov had, enabled them to make a real impact on the establishment of the dialogue between Christians and Jews in particular in the “Beilis affair”.